2021
DOI: 10.3390/toxics9120345
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Composition and Electrophilicity in Vaping Emissions of Flavored and Unflavored E-Liquids

Abstract: It has been demonstrated that propylene glycol (PG), vegetable glycerin (VG), and flavoring chemicals can thermally degrade to form carbonyls during vaping, but less is known about carbonyl emissions produced by transformation of flavoring chemicals and the interactive effects among e-liquid constituents. This study characterized carbonyl composition and levels in vaping emissions of PG-VG (e-liquid base solvents) and four e-liquid formulations flavored with trans-2-hexenol, benzyl alcohol, l-(-)-menthol, or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Ketene, which has an approximate boiling point of −56 °C, was not expected to be observed in our collection. In addition, observation of carbonyl-containing compounds from GC/MS often requires derivatization methods that were not used in this study. , As such, it is highly likely that ketene and other higher volatility compounds are produced during the vaping process but cannot be observed in our results.…”
Section: Results and Discussionmentioning
confidence: 96%
“…Ketene, which has an approximate boiling point of −56 °C, was not expected to be observed in our collection. In addition, observation of carbonyl-containing compounds from GC/MS often requires derivatization methods that were not used in this study. , As such, it is highly likely that ketene and other higher volatility compounds are produced during the vaping process but cannot be observed in our results.…”
Section: Results and Discussionmentioning
confidence: 96%
“…Furthermore, a study by Jaegers et al [44] found that pyrolysis alone in an anaerobic environment was not able to induce thermal degradation of PG and VG at low temperatures (< 200˚C), despite previous studies observing degradation at temperatures as low as 149˚C during vaping [45]. However, when heated in an aerobic environment, thermal decomposition was observed at 133 and 175˚C, both without and with the addition of metal oxides Cr 2 O 3 and ZrO 2 [44], suggesting that oxidation is a key process during vaping.…”
Section: Plos Onementioning
confidence: 94%
“…For example, ketene, which is expected to form during VEA pyrolysis, has an estimated boiling point of -56˚C [30] and, as a result, was not expected to be observed in our collection. Furthermore, highly volatile and/or reactive compounds such as ketene and various low molecular weight carbonyl-containing species, etc., often require additional derivatization methods that were not used in this study to be observed using GC/MS [7,45].…”
Section: Limitationsmentioning
confidence: 99%
“…Individual flavorants in e-liquids could thermally degrade to contribute to the levels of HPHC formation. Trans -cinnamaldehyde (an α,β-unsaturated aldehyde) could undergo nucleophilic attack at the β–carbon to produce acrolein similar to trans -2-hexenal . However, specific degradation of flavorants will be limited by the amount of flavorant present, which is typically small relative to PG and GL.…”
Section: Resultsmentioning
confidence: 99%